Challenges of research management centers to promote collaborative research approach - Quitian-Feliciano, Iván Darío; Rodríguez-González, Gina Liseth; Morales-Rubiano, María Eugenia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective is to identify the challenges of the research centers of the Universidad Militar Nueva Granada, to carry out collaborative research. The Research had a mixed focus. For this, 19 surveys were conducted to leaders of the research groups and 8 interviews with directors of the research centers. It was identified that for 95% of the respondents it was important that the University promoted collaborative research, because it is enriching for their activity as researchers. However, the University's goals and requirements in relation to the type of external researcher with whom they must carry out collaborative research are very high, with 83% of the respondents disagreeing. Among the most relevant findings are the challenges that the directors of the research centers face, such as the need to foster scientific networks, rigidity and excessive internal administrative procedures, the professional profile of researchers and the lack of incentives. It concludes with the need to make the requirements for collaborative research more flexible on the part of the university, so as to promote greater participation by researchers in these activities.